Family Strength in Remote Marriage: Social Support, Coping Strategies, and Their Effects: Family Strength in Remote Marriage: Social Support, Coping Strategies, and Their Effects (Journal of Family Sciences, 2022)
Many married couples in Indonesia have carried out long-distance marriages. It happens because the couple is working or going to school. This study aimed to analyze social support and coping strategies and their effect on the strength of families undergoing long-distance marriages. The research was carried out for nine months, namely February-October 2020. The number of respondents in this study was 60 wives who lived in the ex-Pekalongan Residency, namely Batang Regency, Pekalongan City and Regency, Pemalang Regency, Tegal City, and Regency, and Brebes Regency. This research uses a non-probability sampling method with a voluntary sampling technique. They are collecting data using an online questionnaire, namely through a google form. To analyze the influence of variables used, a multiple linear regression test: results, family support and family strength in the medium category. Wives are more likely to use coping strategies that focus on emotions than those that focus on problems. Based on the regression test results, the husband's length of education has a significant positive effect on family strength in long-distance marriages. The research implies that efforts to improve education, especially for husbands, are needed because it affects family strength.